Energy Transitions: Reflections on the state of Ghana’s Oil and Gas Industry. - (:unkn) unknown (University of Ghana., 2023)
Commercial crude oil production in Ghana began in 2010 after its discovery in 2007, which sparked a renewed hope of economic recovery. Ghana has three main production fields: the Jubilee Field, TEN Field, and Sankofa Gye Nyame (SGN) Field. Currently, other oil blocks are undergoing exploration and could increase the country’s production profile if successful discoveries are made. The oil and gas sector provides an avenue for supporting the national budget through the Annual Budget Funding Amount (ABFA), smoothens budget shortfalls through the Stabilisation Fund and provides funding for future generations through the Heritage Fund. Between 2013 and 2021, the oil and gas sector contributed an average of 4.5% to Ghana’s Gross Domestic Product (GDP) out of about 20 subsectors. Again, natural gas from Ghana’s fields provides fuel for electricity generation through thermal power plants. In 2021, domestic gas formed about 85% of Ghana’s gas demand for power generation. Beyond power generation and support to the budget, the sector also provides direct and indirect employment and supports other sectors of the economy through forward and backward linkages. The current conversation about climate action has heightened the push to transition from fossil-based fuels to cleaner energy sources with possible implications for Ghana’s nascent oil and gas industry. For example, there are fears that Ghana would lose out on the benefits of oil production due to stranded assets occasioned by the transition. Nonetheless, the transition could be advantageous to the country if Ghana positions itself to benefit from the social, economic, and environmental opportunities it presents. Therefore, it is essential for policy to harmonise and balance the trade-offs that exist between oil and gas exploration and clean energy integration. As part of activities marking the 75th Anniversary of the University of Ghana which is under the theme: Nurturing Resilience: Adopting Technology, Embracing Humanism, this dialogue offers the opportunity for a thorough discussion of the future of Ghana’s oil and gas sector through the lenses of the energy transition. In addition, it seeks to answer critical questions of how Ghana can benefit from the energy transition and oil and gas exploration. Lastly, the dialogue highlights the expected action by key institutions in Ghana’s energy sector, which would lead to a maximum benefit of oil and gas and the energy transition.
Keywords: Energy Transitions; Ghana’s Oil; Gas Industry